2014
DOI: 10.2169/internalmedicine.53.2502
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Factors Associated with Mortality within Six Months after Admission among Hospitalized HIV-1 Patients in Shenyang, China

Abstract: Objective Short-term mortality rates remain high among critically ill human immunodeficiency virus-1 (HIV-1) patients though long-term mortality rates have dropped. Baseline risk factors for short-term mortality have not yet been determined in China. In this paper, we herein describe clinical characteristics, laboratory findings, causes of clinical deterioration, and risk factors associated with mortality among HIV-1 patients within six months after hospital admission. Methods We carried out a prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…It is noted that hyponatremia, tuberculosis, and being at WHO stage 4 were associated with long-term mortality, a finding that is consistent with those from our previous short-term mortality study. [25] Although hyponatremia is a common abnormality in patients with adrenal insufficiency, we did not find any correlation between cortisol levels and hyponatremia in this study. During severe illness, sustained hypercortisolism, as opposed to significant DHEA-S depletion, could theoretically result in an imbalance between the immunosuppressive and immunostimulatory pathways [26] and, therefore, play a role in increasing susceptibility to infectious complications.…”
Section: Discussioncontrasting
confidence: 73%
“…It is noted that hyponatremia, tuberculosis, and being at WHO stage 4 were associated with long-term mortality, a finding that is consistent with those from our previous short-term mortality study. [25] Although hyponatremia is a common abnormality in patients with adrenal insufficiency, we did not find any correlation between cortisol levels and hyponatremia in this study. During severe illness, sustained hypercortisolism, as opposed to significant DHEA-S depletion, could theoretically result in an imbalance between the immunosuppressive and immunostimulatory pathways [26] and, therefore, play a role in increasing susceptibility to infectious complications.…”
Section: Discussioncontrasting
confidence: 73%
“…Severe hyponatremia, unlike other electrolyte disorder, is associated with a lower CD4 count. [2628] This may be the plausible reason behind association of hyponatremia with higher morbidity and mortality in HIV patients. There was a significant negative correlation of CD4 count with proteinuria in our study, similar to prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study had a limited follow-up of one year after initiation of antiretroviral therapy in patients with a high mortality (8%) mainly due to tuberculosis (32%). More recently a prospective cohort study of 141 hospitalized patients with advanced stages of HIV infection in China showed that baseline hyponatremia was present in 28.4% of patients and independently associated with three-fold increase of death within six months after admission [ 27 ]. In this study, 72.9% of patients had advanced HIV disease [World Health Organization (WHO) stage 4] and 21.3% of patients died during the first six months of admission which is higher than the short-term mortality rates in other studies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%